A perivascular niche for multipotent progenitors in the fetal testis. Issue 1 (December 2018) - Kumar, Deepti; DeFalco, Tony
Abstract Androgens responsible for male sexual differentiation in utero are produced by Leydig cells in the fetal testicular interstitium. Leydig cells rarely proliferate and, hence, rely on constant differentiation of interstitial progenitors to increase their number during fetal development. The cellular origins of fetal Leydig progenitors and how they are maintained remain largely unknown. Here we show that Notch-active, Nestin-positive perivascular cells in the fetal testis are a multipotent progenitor population, giving rise to Leydig cells, pericytes, and smooth muscle cells. When vasculature is disrupted, perivascular progenitor cells fail to be maintained and excessive Leydig cell differentiation occurs, demonstrating that blood vessels are a critical component of the niche that maintains interstitial progenitor cells. Additionally, our data strongly supports a model in which fetal Leydig cell differentiation occurs by at least two different means, with each having unique progenitor origins and distinct requirements for Notch signaling to maintain the progenitor population. Leydig cells are steroidogenic cells in the testes and produce the androgens required for male development and spermatogenesis. Here the authors show that a multipotent progenitor population producing Leydig cells, pericytes and smooth muscle cells is maintained in a perivascular niche within the mouse fetal testis.